2022
DOI: 10.1002/qua.27067
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of HF and (HF)2 inside a fullerene cage: An in silico study using different density functionals

Abstract: An in silico study on the properties of HF and its dimer inside C60 using density functional theory (DFT) based approaches is presented. For this purpose, 10 different DFT functionals following Jacob's Ladder have been chosen. The geometrical parameters such as bond length and bond angle, of the molecules and their dipole moment have been computed. Two types of orientations, namely, L‐shaped and anti‐parallel of (HF)2 inside C60 are considered, the latter with an extremely short hydrogen bond. HF bond lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The positive sign( λ 2 )ρ represents steric effects due to cages, and the values near zero denote the vdW interactions . Poddar et al recently reported that encapsulation of the HF dimer inside C 60 is not stable . In general, it can be assumed that the encapsulation of the heteroatomic dimer in C 60 is not energetically favorable due to the steric interaction between the cage and molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive sign( λ 2 )ρ represents steric effects due to cages, and the values near zero denote the vdW interactions . Poddar et al recently reported that encapsulation of the HF dimer inside C 60 is not stable . In general, it can be assumed that the encapsulation of the heteroatomic dimer in C 60 is not energetically favorable due to the steric interaction between the cage and molecules.…”
Section: Resultsmentioning
confidence: 99%
“…recently reported that encapsulation of the HF dimer inside C 60 is not stable. 78 In general, it can be assumed that the encapsulation of the heteroatomic dimer in C 60 is not energetically favorable due to the steric interaction between the cage and molecules.…”
Section: Spin Densitymentioning
confidence: 99%